TANTANGAN IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI PELOSOK KALIMANTAN TIMUR - Anthonius Margono; . Supian; . Iyan (Jurnal Administrative Reform, 2019)
This study describes the challenges of implementing the National Program for Community Empowerment (PNPM) Mandiri in East Kalimantan in the perspective of community participation. Qualitative method with descriptive approach used in this study. The research findings show that the challenges of implementing PNPM Mandiri are described from internal and external aspects. Community participation in planning is still at the level of consultation, and implementation is still limited to physical participation not at the level of ideas, due to various limitations.Keywords: challenges, PNPM, participation.